2021
DOI: 10.1038/s43587-020-00006-2
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong restriction of dietary branched-chain amino acids has sex-specific benefits for frailty and life span in mice

Abstract: Protein restricted (PR) diets promote health and longevity in many species. While the precise components of a PR diet that mediate the beneficial effects to longevity have not been defined, we recently showed that many metabolic effects of PR can be attributed to reduced dietary levels of the branched-chain amino acids (BCAAs) leucine, isoleucine, and valine. Here, we demonstrate that restricting dietary BCAAs increases the survival of two different progeroid mouse models, delays frailty and promotes the metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
163
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(173 citation statements)
references
References 100 publications
(150 reference statements)
8
163
2
Order By: Relevance
“…In contrast, Richardson et al suggested that lifelong restriction of dietary BCAAs may extend lifespan and prevent frailty in aged male mice. Nonetheless, the effect of the BCAA diet on frailty remains unclear ( 87 ). Further studies are needed to examine these associations in humans.…”
Section: Types Of Crmentioning
confidence: 99%
“…In contrast, Richardson et al suggested that lifelong restriction of dietary BCAAs may extend lifespan and prevent frailty in aged male mice. Nonetheless, the effect of the BCAA diet on frailty remains unclear ( 87 ). Further studies are needed to examine these associations in humans.…”
Section: Types Of Crmentioning
confidence: 99%
“…In flies, restriction of Methionine extends lifespan, but only under conditions of low amino acid status 25 . In mice, EAA supplementation nullified DR’s lifespan extension 26 and restriction of particular amino-acids, namely branched-chained, can confer health but not necessarily lifespan benefits 1,7,27 .…”
Section: Introductionmentioning
confidence: 99%
“…Such a revelation is somewhat unexpected, but consistent with the observation made in liver-specific Tsc1 knockout and Gcn2 knockout mice by the authors. Yu et al [5] demonstrated that isoleucine restriction mediated beneficial effects were not affected in these mice, implicating an mTOR and Gcn2 independent mechanism, both pathways are known mediators of leucine induced signaling in cells. Instead, from transcriptome analysis in liver and adipose tissues, authors identified a significant perturbation in FGF21 expression and energy expenditure following isoleucine restriction, which was necessary for low-isoleucine diet mediated metabolic protection in mice.…”
mentioning
confidence: 95%
“…However, extensive evidence suggests each of the BCAA may have unique and distinct function in metabolic regulation and nutrient signaling. In a subsequent study by the same group, Yu et al [5] further delineated the specific role of each individual BCAA in dietary impact on metabolic health.…”
mentioning
confidence: 99%
See 1 more Smart Citation